The Effects of Socially Responsible Dimensions on Risk Dynamics and Risk Predictability: A Value-at-Risk Perspective - Viviani, Jean-Laurent; Fall, Malick; Revelli, Christophe (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
Using a Value-at-Risk (VaR) approach and a sample of 2082 stocks on the 2004-2015 period, we measure the impact of SR dimensions (measured by Vigeo ratings) on the risk level and the risk dynamic of stock returns and on their risk predictability. We conclude that good overall socially responsible (SR) ratings reduce the downside risk level of stock returns. We find also that high-rated companies in HR (Human Resources), ENV (Environment), BB (Business Behaviour), CIN (Community Involvement), and HRTS (Human Rights at Workplaces) dimensions better absorb volatility shocks.